Nutrition and management of glycemia in neonates with neonatal encephalopathy treated with hypothermia. Issue 4 (August 2021) - Pinchefsky, E.F.; Schneider, J.; Basu, S.; Tam, E.W.Y.; Gale, C.; ,
Abstract: Adequate nutrition and glycemic homeostasis are increasingly recognized as potentially neuroprotective for the developing brain. In the context of hypoxia-ischemia, evidence is scarce regarding optimal nutritional support and administration route, as well as the short- and long-term consequences of such interventions. In this review, we summarize current knowledge on disturbances of brain metabolism of glucose and substrates by hypoxia-ischemia, and compound effects of these mechanisms on brain injury characterized by specific patterns on EEG and MRI. Risks and benefits of nutrition delivery via parenteral or enteral routes are examined. Nutrition could mitigate adverse neurodevelopmental outcomes, and the impact of nutritional strategies and specific nutritional interventions are reviewed. Limited literature highlights the need for further studies to understand the changes in energy metabolism during and after hypoxic-ischemic injury, to optimize nutritional regimens and glucose management, and to inform the neuroprotective role of nutrition.